La collezione Peggy Guggenheim. - Barr, Alfred H. Jr.; Read, Herbert; Sandberg, Willem (Venezia : Peggy Guggenheim Collection)
Admiral, Virginia ; Appel, Karel ; Archipenko, Aleksandr ; Armitage, Kenneth ; Arp, Hans (Jean) ; Bacci, Edmondo ; Bacon, Francis ; Balla, Giacomo ; Baziotes, William ; Boccioni, Umberto ; Brancusi, Constantin ; Braque, Georges ; Brauner, Victor ; Buggiani, Paolo ; Butler, Reg ; Calder, Alexander ; Campigli, Massimo ; César ; Chadwick, Lynn ; Chagall, Marc ; De Chirico, Giorgio ; Congdon, William ; Consagra, Pietro ; Dali, Salvador ; Davie, Alan ; Delaunay, Robert ; Delvaux, Paul ; van Doesburg, Theo ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Ernst, Max ; Ferber, Herbert ; Ferren, John ; Fini, Leonor ; Garelli, Franco ; Giacometti, Alberto ; Gleizes, Albert ; Gonzales, Julio ; Gorky, Arshile ; Gris, Juan ; Hare, David ; Hartigan, Grace ; Hartung, Hans ; Hayter, Stanley William ; Hélion, Jean ; Hirshfield, Morris ; Hundertwasser ; Irwin, Gwther ; Jenkins, Paul ; Kandinsky, Wassily ; Klee, Paul ; Koenig, Fritz ; de Kooning, Willem ; Lardera, Berto ; Lassaw, Ibram ; Leger, Fernand ; Lipchitz, Jacques ; Lissitzky, El ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Marcoussis, Louis ; Marini, Marino ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Metzinger, Jean ; Minassian, Leone ; Minguzzi, Luciano ; Mirko ; Miro, Joan ; Mondriaan, Piet ; Moore, Henry ; Motherwell, Robert ; Nicholson, Ben ; Ozenfant, Amédée ; Paolozzi, Eduardo ; Pegeen ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pirandello, Fausto ; Pollock, Jackson ; Prampolini, Enrico ; Richter, Germaine ; Rothko, Mark ; Santomaso, Giuseppe ; Scalini, Giuditta ; Schwitters, Kurt ; Scott, Kenneth ; Severini, Gino ; Sobel, Janet ; Still, Clyfford ; Takis ; Tancredi ; Tanguy, Yves ; Thornton, Leslie Tillotson ; Toyofuky, Tomonori ; Tunnard, John ; Vail, Lawrence ; etc.
La collezione Peggy Guggenheim a visible a Palazzo Venier dei Leoni, Venezia
Frans & Engels
boek